Deceleration capacity as a risk predictor in patients presenting to the emergency department with syncope: A prospective exploratory pilot study. Issue 49 (December 2017) - Duckheim, Martin; Klee, Katharina; Götz, Nina; Helle, Paul; Groga-Bada, Patrick; Mizera, Lars; Gawaz, Meinrad; Zuern, Christine S.; Eick, Christian
Abstract : Abstract: Syncope is a common cause for admission to the emergency department (ED). Due to limited clinical resources there is great interest in developing risk stratification tools that allow identifying patients with syncope who are at low risk and can be safely discharged. Deceleration capacity (DC) is a strong risk predictor in postinfarction and heart failure patients. The aim of this study was to evaluate whether DC provides prognostic information in patients presenting to ED with syncope. We prospectively enrolled 395 patients presenting to the ED due to syncope. Patient's electrocardiogram (ECG) for the calculation of DC was recorded by monitoring devices which were started after admission. Both the modified early warning score (MEWS) and the San Francisco syncope score (SFSS) were determined in every patient. Primary endpoint was mortality after 180 days. Eight patients (2%) died after 180 days. DC was significantly lower in the group of nonsurvivors as compared with survivors (3.1 ± 2.5 ms vs 6.7 ± 2.4 ms; P  < .001), whereas the MEWS was comparable in both was comparable in both groups. (2.1 ± 0.8 vs 2.1 ± 1.0; P  = .84). The SFSS failed at identifying 4 of 8 nonsurvivors (50%) as high risk patients. No patient with a favorable DC (≥7 ms) died (0.0% vs 3.7%; P  = .01, OR 0.55 (95% CI 0.40–0.76), P  < .001). In the receiver operating characteristic (ROC) analysis DC yielded an area under the curve of 0.85 (95% CI 0.71–0.98). Our study demonstrates that DC is a predictor of 180-days-mortality in patients admitted to the ED due to syncope. Syncope patients at low risk can be identified by DC and may be discharged safely.